Girl One - Murphy, Sara Flannery (New York : MCD / Farrar, Straus and Giroux, 2021)
"A dark ode to power and femininity, about a young woman whose search for her missing mother reveals the secrets of her past--including her time spent on the Homestead as one of nine babies born via parthenogenesis"--.